TARGIT-E(lderly): prospective phase II study of intraoperative radiotherapy (IORT) in elderly patients with small breast cancer - Neumaier, Christian; Sperk, Elena; Welzel, Grit; Abo-Madyan, Yasser; Kraus-Tiefenbacher, Uta; Keller, Anke; Gerhardt, Axel; Sütterlin, Marc; Wenz, Frederik (BMC cancer, 2012)
Patients ≥ 70 years with small, low-risk breast cancer who are operated but not irradiated how local relapse rates around 4% after 4 years. With adjuvant whole breast radiotherapy (WBRT) the local relapse rate drops to 1% after 4 years under Tamoxifen. It has been demonstrated that the efficacy of radiotherapy of the tumor bed only in a selected group can be non-inferior to WBRT.
In der Verfasserangabe sind Vorname und Nachname der meisten Verfasser vertauscht
Gesehen am 28.08.2018